CORRELATION BETWEEN RICE HUSK ASH AS SUBSTITUTION MATERIALS THE AMOUNT OF CEMENT AND PROPERTIES OF HIGH STRENGTH FLOWING CONCRETE - Surya Sebayang (UNIVERSITAS LAMPUNG, 2011)
Flowing concrete flow under it own weight and maintain homogeneity while filling and passing around congested reinforcement. Flowing concrete is used to reduce or eliminate the need for vibration to reduce construction cost and reducing construction time. High strength flowing concrete in this research used rice husk ash as substitution material the amount of cement. The properties investigated are workability, concrete setting time, and compression strength.Proportion of material for concrete determined according to ACI 211-4R-1993 and combine with Hashimoto method. The substitution of rice husk ash to the concrete are 0 %, 3%, 6%, 9%, 12% and 15% of the cement content. The test result indicated that effect of rice husk ash in fresh concrete was increased the workability of the concrete. Addition of rice husk ash was made fresh concrete enough cohesiveness without causing segregation. Addition of rice husk ash was increased the initial and final setting time. The cylinder compression strength of rice husk ash flowing concrete at 7day and 14 days was lower than compression strength of flowing concrete without rice husk ash at the same days. The optimum strength of rice husk ash flowing concrete was 44,44 MPa at 56 days age in 12 % presence of rice husk ash.